An Analysis of Grammatical Errors on Academic Essays Written by Students of STBA LIA Yogyakarta - Fifi Ayu Ratnaningrum; Hesthi Herusatoto; Nugraha krisdiyanta (Conscientia, 2020)
This thesis is an analysis of grammatical errors written by students of STBA LIA Yogyakarta, academic year of 2011/2012. The aims of this thesis were to find out the most common grammatical errors in the academic essay written by the students of STBA LIA Yogyakarta and to find out the possible causes of errors. Errors are part of learning, difficult enough to avoid. To study students’ errors, the approach that was used was Corder’s error analysis. The error analysis included identification, description and explanation errors. The grammatical error types were categorized into errors of overgeneralization, transfer, and simplification by omission. The result indicated that the errors made by the students were mostly in simplification by omission (60 times) followed by overgeneralization (35 times) and transfers (7 times). Those errors were caused by interference of mother tongue and learning strategies which are false analogy, incomplete rule application, and overlooking co-occurrence.